2015
DOI: 10.1186/s12879-015-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide prevalence of human papillomavirus infection and viral genotype distribution in 37 cities in China

Abstract: BackgroundType-specific high-risk HPV (hrHPV) infection is related to cervical carcinogenesis. The prevalence of hrHPV infection varies geographically, which might reflect the epidemiological characteristics of cervical cancer among different populations. To establish a foundation for HPV-based screening and vaccination programs in China, we investigated the most recent HPV prevalence and genotypic distributions in different female age groups and geographical regions in China.MethodsIn 2012, a total of 120,772… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
154
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(218 citation statements)
references
References 47 publications
37
154
21
Order By: Relevance
“…According to Winer and colleagues, the actual first peak of HPV infection might be before the age of 25 years, as women are usually infected after sexual initiation [29]. HPV16 and 18 types have been found to be the most prevalent high risk types in most studies [4, 2628, 3032], yet in the current study we were not able to establish that. However, we observed high frequency of hr-HPV31/33/35/52/58 group types among the study population.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…According to Winer and colleagues, the actual first peak of HPV infection might be before the age of 25 years, as women are usually infected after sexual initiation [29]. HPV16 and 18 types have been found to be the most prevalent high risk types in most studies [4, 2628, 3032], yet in the current study we were not able to establish that. However, we observed high frequency of hr-HPV31/33/35/52/58 group types among the study population.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies conducted in Tanzania and Nigeria found high prevalence of HPV (20.1% and 14.7% respectively) [23, 25]. In China the prevalence of HPV infection was found to vary between regions from 13.8%–44.4% [28]. A higher prevalence of above 75% was observed in two studies conducted in Brazil [22, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The five most prevalent HPV genotypes in our sample were HPV52, 58, 33, 68 and 16, similar to that in HIV- women in Guangxi province 5. And HPV 52, 58 are consistently the most prevalent HPV subtypes nationwide 6. These evidences suggest that HPV coinfection is consistently high in Chinese WLHIV and does not exhibit substantial geographical variations.…”
Section: Discussionmentioning
confidence: 77%
“…A more worrying trend is that cervical cancer is occurring earlier and causing death in younger age groups in some developed urban areas (43). With the increasing prevalence of HPV infection especially in young women, combined with inadequate Papanicolaou (Pap) test screening and poor uptake of HPV vaccines, cervical cancer will continue to pose a huge public health burden to mainland China (2,44). Therefore, effective prevention and control strategies need to be identified.…”
Section: Resultsmentioning
confidence: 99%